PEMANFAATAN TEPUNG DAUN TURI(Sesbania grandiflora) HASIL FERMENTASI TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN GURAMI (Osphronemous gouramy) - sri wahyuni; Salnida Yuniarti Lumbessy; Dewi Nur’aeni Setyowati (Journal of Fish Nutrition, 2022)
The aim of this study was to determine the growth and survival of gouramy fish fed fish feed with the addition of fermented turi leaf flour. This study used an experimental method using a completely randomized design (CRD) using four treatments and three replications, namely P1 (without giving fermented turi leaves) P2 (10% fermented turi leaves), P3 (15% fermented turi leaves), P4 (20% fermented turi leaves), then direct test was performed using analysis of variance (ANOVA). The research parameters included absolute weight (BM), absolute length (PM), specific growth rate (SGR), feed conversion ratio (FCR), feed efficiency (EPP), survival rate (SR) and water quality. The results of this study showed that feeding with the addition of fermented turi leaves had no significant effect on absolute weight (BM), absolute length (PM), specific growth rate (SGR), feed conversion ratio (FCR), feed efficiency (EP) and survival rate ( SR).